Assessment of environmental determinants of physical activity: a study of built environment indicators in Brno, Czech Republic - Brázdová, Zuzana; Klimusová, Helena; Hruška, Dušan; Prokopová, Alice; Burjanek, Aleš; Wulff, Krauff Rainer Schwanhaeuser (Central European Journal of Public Health, 2015)
BACKGROUND: Research on physical activity in relation to obesity gradually becomes more focused on environmental determinants, which can potentially influence people's health choices. The present article addresses the topic of physical activity from a wider sociological perspective. Our pilot study was designed with the objective of testing the applicability of a method included in the EC 6th Framework Programme EURO-PREVOB, in the Czech context. The method examines specific determinants of the built environment that can have an impact on physical activity at the population level. In addition, the study aims to analyze possible differences in built environment indicators and their relation to the physical activity of people living in neighbourhoods with areas of varying socioeconomic status. METHODS: The field study was carried out in the city of Brno, Czech Republic, in 5 neighbourhood quintiles, i.e. areas divided according to the socioeconomic status of local residents. In each quintile, we evaluated the quality of the built environment according to the quality, aesthetics and safety of segregated cycle facilities, playgrounds/playing areas, public open spaces, marked road crossings and pavements as well as signs of incivilities and devastation. RESULTS: Between the five quintiles, significant differences were found in the quality of parks and playgrounds/playing areas, pavements, marking of pedestrian crossings, and in general aesthetics, i.e. signs of incivilities and devastation of the built environment. No differences were found in the quality and use of cycle facilities. CONCLUSIONS: The method we used for the evaluation of the built environment proved highly applicable in Czech populated areas. Monitoring of built environment indicators in the Czech Republic should provide a basis for health maps, showing potential associations between the prevalence of high-incidence, non-infectious diseases and various social determinants of physical activity. This information might help in achieving an improvement in these determinants at a community level and promoting an increase in physical activity at the population level.
Keywords: Female; charakteristiky bydlení; ženské pohlaví; pohybová aktivita; lidé; hra a hračky; Pilot Projects; Environment Design; pilotní projekty; Esthetics; Risk Factors; Residence Characteristics; Male; Czech Republic; Socioeconomic Factors; životní prostředí - projekt; Play and Playthings; rizikové faktory; Česká republika; Motor Activity; socioekonomické faktory; mužské pohlaví; estetika; Humans